Basel III capital buffer requirements and credit union prudential regulation: Canadian evidence - Hessou, Helyoth; Lai, Van Son (Journal of Financial Stability, 2017)
Some Canadian provinces have already adopted Basel III rules for the oversight of their administrated credit unions. We analyze the importance of the Basel III additional capital buffer requirements for credit union prudential regulation. Based on a sample of the 100 largest credit unions in Canada from 1996 to 2014, we find that Canadian credit union capital buffers behave countercyclically over the business cycle. Further, credit unions hold a capital buffer bigger than the maximum buffer advocated under Basel III which is 5% of risk-weighted assets (RWA). These results suggest that, unlike commercial banks worldwide, credit unions, by and large, are already in compliance with the new Basel III buffer requirements. However, there is evidence that the capital buffers of low-capitalized credit unions are procyclical. These credit unions increased their RWA during booms but failed to build up additional capital accordingly. Hence, weakly capitalized credit unions are more likely to adjust their capital buffers if they are subject to Basel III capital buffer regulation.